Analisis Mutu Pelayanan Rawat Inap Menggunakan Jendela Pelanggan di RSUD Kalisat Jember - Eko Hari Wibowo; IGN Arya Sidemen; Alice Anjarsari (Jurnal Ilmu Kesehatan Masyarakat, 2009)
The inpatient service at Kalisat General Hospital has been a prominent product for the community in Kalisat and its vicinity. However, the service exploiting was  not yet optimal. BOR of the hospital in the years 2007 equal to 59% where was still under from ideal BOR of hospital that is 75%-85%. The research aims to analyzed the  inpatient service quality based on customer window analysis. The research was using cross sectional survey design through questionnaires. Sample research represents a total population at range of time 16-25 June 2008 amounting to 109 respondents. The research result showed that the percentage of concurrence between expectation and service to input equal to 90.60% and process equal to 96.16%. Based on distribution of 30 factors on the customer window diagram, there are 8 factors on A quadrant where is put as first priority for improvement, 15 factors on B quadrant where is  the service performance is needed to be defended, 2 factors on C quadrant where is needed to promote this important to the patient, and 5 factors on D quadrant  where is getting the low priority for improvement. Keywords: expected and perceived service, inpatient service quality, customer window